Analysis of Frusemide by Application of Hydrotropic Solubilization Phenomenon in Solid Dosage Form - MAHESHWARI, R.K.; PANDEY, S.P.; RAMCHANDANI, U.; GUPTA, H.M. (Asian Journal of Chemistry, 2010)
In the present investigation, frusemide has been selected as a poorly water-soluble model drug. There was more than 30-fold enhancement in aqueous solubility of frusemide by 2.0 M sodium salicylate (as compared to aqueous solubility). This hydrotropic agent was employed to solubilize drug from the fine powder of tablet formulations. The hydrotropic agent and the additive used in formulation did not interfere in analysis. Proposed method is new, simple, accurate and reproducible. Statistical data proved the accuracy, reproducibility and the precision of the method.